Alzheimer's disease neuropathology in the hippocampus and brainstem of people with obstructive sleep apnea. Issue 3 (21st September 2020) - Owen, Jessica E; Benediktsdottir, Bryndis; Cook, Elizabeth; Olafsson, Isleifur; Gislason, Thorarinn; Robinson, Stephen R
Abstract: Obstructive sleep apnea (OSA) involves intermittent cessations of breathing during sleep. People with OSA can experience memory deficits and have reduced hippocampal volume; these features are also characteristic of Alzheimer's disease (AD), where they are accompanied by neurofibrillary tangles (NFTs) and amyloid beta (Aβ) plaques in the hippocampus and brainstem. We have recently shown reduced hippocampal volume to be related to OSA severity, and although OSA may be a risk factor for AD, the hippocampus and brainstems of clinically verified OSA cases have not yet been examined for NFTs and Aβ plaques. The present study used quantitative immunohistochemistry to investigate postmortem hippocampi of 34 people with OSA (18 females, 16 males; mean age 67 years) and brainstems of 24 people with OSA for the presence of NFTs and Aβ plaques. OSA severity was a significant predictor of Aβ plaque burden in the hippocampus after controlling for age, sex, body mass index (BMI), and continuous positive airway pressure (CPAP) use. OSA severity also predicted NFT burden in the hippocampus, but not after controlling for age. Although 71% of brainstems contained NFTs and 21% contained Aβ plaques, their burdens were not correlated with OSA severity. These results indicate that OSA accounts for some of the "cognitively normal" individuals who have been found to have substantial Aβ burdens, and are currently considered to be at a prodromal stage of AD.